Direct Elimination of Detrimental Surface Phases Parasitic to LiNixCo1−xO2 (x = 0.8 and 0.9) with Unique 3D Porous Structures during Synthesis. Issue 13 (13th June 2021) - Tan, Xinghua; Guo, Limin; Zhao, Tingqiao; Mao, Dongdong; Jiang, Mingyan; Nie, Shuai; Song, Luting; Kang, Xiaohong; Wang, Hanfu; Sun, Lianfeng; Chu, Weiguo
Abstract: Detrimental rock‐salt and/or spinel surface phases parasitic to Ni‐rich layered oxides with high theoretical capacity are quite formidable which are reported to be eliminated only through alien element dopings and/or surface modifications. Herein, these surface phases are directly eliminated successfully during the synthesis of pristine LiNi0.8 Co0.2 O2 and LiNi0.9 Co0.1 O2 using an expanded graphites (EGs) template approach, accompanied by the formation of unique 3D porous structures. The elimination of surface phases may be ascribed to the 3D porous structures formed during the calcination processes at both low and high temperatures, which enables the access of sufficient oxygen to individual nanoparticles and thus promotes the oxidization of Ni 2+ to Ni 3+ to reduce Li/Ni disordering. Both LiNi0.8 Co0.2 O2 and LiNi0.9 Co0.1 O2 show excellent rate capability, long‐term cycling stability, and high initial Coulombic efficiencies (ICEs), such as 210.4 (149) and 222.6 (133) mAh g −1, ICEs of 94.9% and 93.8% at 0.1 C (20 C), and capacity retentions of 74% after 500 cycles at 1 C and 76% after 300 cycles at 1 C, respectively, far better than those synthesized using a conventional sol–gel recipe. This study provides a simple and novel platform for directly synthesizing detrimental surface phases free and chemically stoichiometric Ni‐rich layered oxides with high performance. Abstract : An approach is proposed to directly eliminate detrimental rock‐salt and spinel surface phases for nickel‐rich layered oxides and other electrode oxides with unique 3D porous structures during synthesis without element doping and/or surface modifications involved which is simple, general, cost‐effective, and upscalable. The as‐obtained oxides exhibit superior rate capability and long‐term cycling stability, and high initial Coulombic efficiencies simultaneously.